United States Cyber Attacks On Middle Eastern Countries And Implications For Middle East Geopolitics - Agnia, Tubagus; Muttaqin, Mohammad Izdiyan; Nurwahidin, Nurwahidin (Jurnal Ilmu Sosial Mamangan, 2024)
The Middle East has become the main stage of geopolitical competition between various countries and non-state actors. In this digital era, cyber warfare has become a major instrument in expanding influence and securing interests in the region. US intervention in Middle Eastern countries is quite large, including cyber attacks. Cyber warfare has become an inseparable part of regional conflicts in the Middle East. This occurs in conflict countries such as Syria, Yemen, and Libya. Each has different political, military, and economic interests, triggering a series of cyber attacks and counterattacks. This study aims to determine the influence of US cyber attacks on countries in the Middle East, especially countries in conflict, and to measure the impact of these attacks on the geopolitical conditions of the Middle East. This study uses a library research method, namely a literature study. This method is carried out by taking data from library sources such as theses, journals, or other scientific articles. The findings of this study explain that the United States has a high political tendency towards conflict countries in the Middle East and uses cyberspace as an influential medium to intervene in order to launch attacks and obtain intelligence data.